The ArgR Regulatory Protein, a Helper to the Anaerobic Regulator ANR during Transcriptional Activation of the arcD Promoter in Pseudomonas aeruginosa - Lu, Chung-Dar (American Society for Microbiology, 1999)
Pseudomonas aeruginosa, when deprived of oxygen, generates ATP from arginine catabolism by enzymes of the arginine deiminase pathway, encoded by the arcDABC operon. Under conditions of low oxygen tension, the transcriptional activator ANR binds to a site centered 41.5 bp upstream of the arcD transcriptional start. ANR-mediated anaerobic induction was enhanced two- to threefold by extracellular arginine. This arginine effect depended, in trans, on the transcriptional regulator ArgR and, in cis, on an ArgR binding site centered at −73.5 bp in the arcD promoter. Binding of purified ArgR protein to this site was demonstrated by electrophoretic mobility shift assays and DNase I footprinting. This ArgR recognition site contained a sequence, 5′-TGACGC-3′, which deviated in only 1 base from the common sequence motif 5′-TGTCGC-3′ found in other ArgR binding sites of P. aeruginosa. Furthermore, an alignment of all known ArgR binding sites confirmed that they consist of two directly repeated half-sites. In the absence of ANR, arginine did not induce the arc operon, suggesting that ArgR alone does not activate the arcD promoter. According to a model proposed, ArgR makes physical contact with ANR and thereby facilitates initiation of arc transcription.